Functionality and aesthetics of small-scale renewable energy networks: the need to shift to sustainable resources and designed green energy systems - Ferrara, Nicholas Joseph (Kansas State University, 2021)
Renewable energy is becoming a major part of the energy generating infrastructure used in both the United States and in several nations throughout the world. While there are many technological and engineering issues surrounding renewable energy and its implementation into the current electrical “grid,” there are also various social issues with renewable energy related to public perception and appearance within the landscape. Additionally, the current “grid” system in the United States is nationally connected meaning generated energy is created far from where it is consumed. This focus on nationally produced energy has led to the creation of hundreds of transmission lines spanning thousands of miles and at times interrupting scenic landscapes. The study reported here examines a variety of key texts and case studies to create a general set of design guidelines and recommendations for the creation of small to medium-scale renewable energy landscapes within a specific region, namely eastern Kansas. Initial design guidelines informed the design of four potential renewable energy landscapes throughout the region along the eastern portion of the Kansas river. Two of the site designs in Eudora and De Soto (KS), were selected for further study by conducting a preference test with the local town’s inhabitants and community members. The preference test utilized imagery from the renewable energy sites of both cities to determine respondent’s preferences towards renewable energy type (wind and solar) and their attitudes about local scenery, environmental issues, and the importance of renewable energy. The results suggest that people within eastern Kansas are hesitant to seeing renewable energy within their own landscapes, but that wind energy is preferred to solar energy or some combination of the two. Results also indicated that these people see eastern Kansas landscapes as scenic and that it is important to preserve the scenic attributes and unique character of these landscapes. Results were then used to reform the design guidelines and recommendations previously mentioned and adjust the four potential renewable energy sites accordingly.
Keywords: Renewable energy; Landscape architecture; Sustainability; Landscape aesthetics; Community preferences